La politica industriale tra Stato e Mercato - Carnazza, Paolo (Argomenti, 2016)
This paper aims to analyze the role of industrial policy, in Italy, trying to identify the perspectives either in the short or in medium-long term. After having illustrated the main results of a recent research on the effectiveness of industrial policy, the analysis compares two different approaches: the first aimed at attributing to the State an important role in defining a set of structural economic and industrial measures; the second finalized to minimize the State intervention in support of the productive system. Moreover, the research focuses on the more recent measures of industrial policy adopted in Italy especially for increasing innovation and new firms with high technological content: these interventions appear to outline a real philosophy of industrial policy and can be considered in between the two different visions. In the conclusions, some thoughts are developed in order to indicate the future and desirable trends of industrial policy to be placed inside a Project-Country and shared with medium - long term objectives